The Taste Culture Reader / Experiencing Food and Drink - Korsmeyer Carolyn (Berg, 2005)
This book explores the sensuous dimensions of eating and drinking, from the physiology of the tongue to the embodiment of social identities and enactment of ceremonial meanings. Introduction: Perspectives on Taste, Taste: Physiology and Circumstance, Taste Cultures: Gustation in History, Eloquent Flavors, Body and Souls, Taste and Aesthetic Discrimination, Fine Discernments and the Cultivation of Taste, Taste and Emotion and Memory, Artifice and Authenticity, Succulent Selection: A Select Bibliography of 50 Further Readings, Index.